Superstructure glassy carbon material and application thereof
By designing a three-period extremely small curved surface lattice superstructure and using 3D printing technology to prepare polymer polymer scaffolds, the problems of uncontrollable shrinkage and uneven shape in the preparation of existing glass carbon materials are solved, and the preparation of high-performance and controllable shapes are achieved.
Patent Information
- Application Number
- CN202411880235.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-22
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing preparation methods of glass carbon materials have problems such as uncontrollable shrinkage, uneven shape and structure, and microscopic defects, making it difficult to take into account both mechanical properties and specific shape design.
A three-period extremely small curved surface lattice superstructure design is adopted to prepare polymer polymer scaffolds through 3D printing technology, and pyrolysis is used to obtain an equally reduced superstructured glass carbon material under high temperature conditions.
It has achieved the preparation of superstructured glass carbon materials with large size, controllable pyrolysis deformation, uniform structure and few microscopic defects. It has excellent mechanical properties and adaptability, and is suitable for energy, aerospace, biomedicine and other fields.
Smart Images

Figure CN119591086A_ABST
Abstract
Description
[0001] Priority application This application claims priority to the Chinese invention patent application [CN2024114799352] "A superstructure glassy carbon and its preparation method and application" filed on October 22, 2024, which is incorporated by reference in its entirety. Technical Field
[0002] The invention belongs to the technical field of material preparation, and in particular relates to a superstructure glassy carbon material and application thereof. Background Art
[0003] Glassy carbon is a type of amorphous carbon that usually has good mechanical properties, electrical conductivity, biocompatibility and chemical stability, and has important application value in the fields of biomedicine, energy, aerospace, etc. At present, the preparation method of glassy carbon is usually to pyrolyze polymer precursors at high temperature under vacuum or inert gas. The pyrolysis process will cause a large volume shrinkage, which is easy to cause deformation, foaming, breakage, cracking and other problems, which seriously limits the development and application of glassy carbon materials.
[0004] The existing preparation and application of glassy carbon are subject to severe process limitations, mainly due to problems such as uncontrollable shrinkage, uneven shape and structure, and microscopic defects during firing. In other words, it is currently difficult to prepare glassy carbon materials that have both mechanical properties and specific shape design using existing technologies.
[0005] Patent No. CN116143519A discloses a method for preparing a large-sized medical glassy carbon block material. However, the raw material required for this process is nanodiamond, which is expensive. At the same time, this process is complicated and requires high temperature and high pressure conditions. Patent No. CN116495720A discloses a network glassy carbon and its preparation method. However, the three-dimensional network structure glassy carbon prepared by this method has insufficient mechanical properties and is difficult to meet the needs of many practical applications.
[0006] At present, the research on high-performance structural glassy carbon is still in its infancy. With the development of energy, aerospace, biomedicine and other fields, the demand for high-strength glassy carbon materials with precisely controllable shapes and sizes is becoming more and more urgent. The mechanical properties of existing porous glassy carbon materials are relatively low, and it is difficult to precisely control the shape and size. As the size increases, the mechanical properties of glassy carbon materials will drop significantly, and it will be difficult to further control the shape and size. Therefore, it is necessary to propose improved methods and strategies for the above-mentioned problems existing in the prior art in order to develop high-performance porous glassy carbon materials, thereby promoting the application of glassy carbon materials in multiple fields. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a superstructure glassy carbon material with an innovative structure and a preparation method and application thereof, so as to alleviate or partially alleviate the deficiencies existing in the prior art in the field. The present invention specifically adopts the following technical solutions.
[0008] One aspect of the present invention provides a support structure.
[0009] A porous support structure has a stable structure with uniform stress distribution in all directions; the porous support structure uses a unit cell of a three-periodic minimal surface as a minimum repeating unit; the unit cell of the three-periodic minimal surface includes a diamond or diamond-like structure; and the material constituting the porous support structure is a high molecular polymer.
[0010] Furthermore, the three-periodic minimal surface includes a digital model that satisfies the following characteristics: (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3.
[0011] Furthermore, the high molecular polymer includes a high molecular polymer with a high carbon content.
[0012] As a preferred embodiment, the high molecular polymer with high carbon content comprises furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin, polylactic acid, polycaprolactone, polyethylene, polyetheretherketone, nylon, polycarbonate, polymethyl methacrylate, polyvinyl butyral, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene chloride, polystyrene, polybutadiene, polyphenylene ether, polyphenylene sulfide, polybutene-1, polybenzimidazole, polyaryletherketone, polyarylsulfone, polyethylene naphthalate , polyaniline, polyacetylene, polyparaphenylene, polyphthalimide, polyphenylene vinylene, polylactide, polychloroprene, cyanoacrylate, polynaphthylene vinylene, polyparaxylene, polymethylphenylsiloxane, liquid crystal polymer, polythiophene, polyvinyl acetylene, polyoxadiazole, polybisphenol A, polyacrylonitrile-butadiene-styrene copolymer, polytrifluorochloroethylene, polyepoxy resin-acrylate copolymer, polybenzoquinone, polyparaphenylene sulfone, polyphenylene, polybenzoxazole, polypiperidine, polyvinyl acetal, polybenzothiazole and polyvinyl pyrrolidone. One or more materials selected from the group consisting of.
[0013] Another aspect of the present invention provides a superstructure glassy carbon.
[0014] A superstructure glassy carbon, the superstructure glassy carbon is obtained by pyrolyzing the above-mentioned porous support structure and then carbonizing it in equal proportion; the pyrolysis conditions include vacuum high-temperature pyrolysis or high-temperature and normal-pressure pyrolysis in an inert atmosphere.
[0015] As a preferred embodiment, the vacuum high-temperature pyrolysis or the high-temperature normal-pressure pyrolysis can first be heated from room temperature to 250°C, then to 350°C, kept warm for a period of time, then heated by 1 degree every 2 minutes to 700-3000°C, and then cooled naturally.
[0016] A superstructure glassy carbon, the superstructure glassy carbon having a stable structure with uniformly distributed stress in all directions; the superstructure glassy carbon uses a unit cell of a three-period minimal surface as a minimum repeating unit; the unit cell of the three-period minimal surface includes a diamond or diamond-like structure.
[0017] Furthermore, the surface average curvature of the three-periodic minimal surface structure ranges from -0.135 to 0.137.
[0018] As a preferred implementation, the surface average curvature of the three-periodic minimal surface structure is 0.
[0019] Furthermore, the three-periodic minimal surface includes a digital model that satisfies the following characteristics: (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3.
[0020] Furthermore, the superstructure glassy carbon is obtained by pyrolyzing a high molecular polymer scaffold having the same structural unit and then carbonizing it in equal proportion; the pyrolysis conditions include vacuum high temperature pyrolysis or high temperature and normal pressure pyrolysis under an inert atmosphere.
[0021] The “same structural unit” means that the polymer scaffold also has a stable structure with uniform stress distribution in all directions; it also uses the unit cell of the three-period minimal surface as the minimum repeating unit; the unit cell of the three-period minimal surface includes a diamond or diamond-like structure.
[0022] As a preferred embodiment, the vacuum high-temperature pyrolysis or the high-temperature normal-pressure pyrolysis can first be heated from room temperature to 250°C, then to 350°C, kept warm for a period of time, then heated by 1 degree every 2 minutes to 700-3000°C, and then cooled naturally.
[0023] In some preferred embodiments, the porous support structure or the superstructure glassy carbon has a uniform porous structure, the pore wall thickness of the porous structure is less than 3 mm, and the porosity is greater than 50%, but this is not a limitation.
[0024] In some other embodiments, the porous scaffold structure or the superstructure glassy carbon has a non-uniform porous structure.
[0025] Another aspect of the present invention provides the application of the superstructure glassy carbon.
[0026] The above-mentioned superstructure glassy carbon is used in the preparation of large-size materials, and the specifications of the large-size materials are from millimeter level to decimeter level; preferably, the specifications of the large-size materials include millimeter level, centimeter level or decimeter level.
[0027] Furthermore, the large-size material includes a large-size glassy carbon material and a composite material of large-size glassy carbon and other materials; the other materials include metal materials, polymer materials, ceramic materials, glass materials or semiconductor materials.
[0028] In some preferred embodiments, the size of the large-sized glassy carbon is greater than 5 cm, but is not limited thereto.
[0029] The above-mentioned superstructure glassy carbon is used in the preparation of microscopic complex structure materials, the specifications of the microscopic complex structure materials are from nanometer level to millimeter level; preferably, the specifications of the microscopic complex structure materials include nanometer level, micrometer level or millimeter level.
[0030] Furthermore, the precision of the microscopic complex structure material is from nanometer level to micrometer level. The "precision" is the minimum line width of the support structure printed by the 3D printing method.
[0031] The application of the above-mentioned superstructure glassy carbon in the preparation of energy materials.
[0032] The present invention can also provide an example of a method for preparing the above-mentioned superstructure glassy carbon, which is specifically as follows.
[0033] S01: Design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure, the three-dimensional digital model includes (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3; S02: using the three-dimensional digital model designed and constructed in S01 as a template for 3D printing, wherein the material used for the 3D printing includes a polymer to obtain a polymer scaffold; S03: Pyrolyzing the high molecular polymer scaffold obtained in S02 at high temperature and normal pressure (protected by an inert atmosphere) to obtain the superstructure glassy carbon.
[0034] Furthermore, the bond angle of the three-dimensional digital model is 109.5°.
[0035] Further, the high molecular polymer used in S02 includes furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin, polylactic acid, polycaprolactone, polyethylene, polyetheretherketone, nylon, polycarbonate, polymethyl methacrylate, polyvinyl butyral, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene chloride, polystyrene, polybutadiene, polyphenylene ether, polyphenylene sulfide, polybutene-1, polybenzimidazole, polyaryletherketone, polyarylsulfone, polyethylene naphthalate, polyaniline , polyacetylene, polyparaphenylene, polyphthalimide, polyphenylene vinylene, polylactide, polychloroprene, cyanoacrylate, polynaphthylene vinylene, polyparaxylene, polymethylphenylsiloxane, liquid crystal polymer, polythiophene, polyvinyl acetylene, polyoxadiazole, polybisphenol A, polyacrylonitrile-butadiene-styrene copolymer, polytrifluorochloroethylene, polyepoxy resin-acrylate copolymer, polybenzoquinone, polyparaphenylene sulfone, polyphenylene, polybenzoxazole, polypiperidine, polyvinyl acetal, polybenzothiazole and polyvinyl pyrrolidone. One or more materials selected from the group consisting of.
[0036] Further, SO3 is heated at normal pressure in an inert gas, wherein the inert gas comprises one or more gases selected from the group consisting of nitrogen, argon, helium and neon.
[0037] Furthermore, the 3D printing used in S02 includes liquid crystal display printing technology, digital light processing printing technology, two-photon printing technology, extrusion printing technology or powder laser sintering printing technology.
[0038] Wherein, the bracket can be prepared by direct or indirect 3D printing.
[0039] Direct printing is to directly use 3D printing technology to print out a specific structure.
[0040] Indirect printing is to first print out the mold, and then use the guided mold method to indirectly prepare a specific structure. The specific operations are as follows: S01: Design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure, the three-dimensional digital model includes (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3; S02: constructing a solid model having the same length, width and height as the three-dimensional digital model, subtracting the structure of the three-dimensional digital model from the solid model to obtain a guided mold model, and printing out the guided mold model using 3D printing technology; S03: pouring a high molecular polymer material into the guide mold model, and then burning the guide mold model at a high temperature to obtain a stent structure made of the high molecular polymer; S04: further pyrolyzing the support structure to obtain the superstructure glassy carbon.
[0041] Beneficial technical effects: The present invention aims to resolve the contradiction between the shape, size and mechanical properties of glassy carbon materials by designing a structure with uniform stress, thereby preparing a superstructure glassy carbon that takes both mechanical and shape design into consideration, as specifically described below.
[0042] (1) The present invention designs a three-periodic minimal surface lattice superstructure and utilizes the excellent stress uniform distribution behavior of the lattice structure during pyrolysis shrinkage to prepare a superstructure glassy carbon with large size, controllable pyrolysis deformation, uniform structure and few microscopic defects.
[0043] (2) The present invention adopts the existing 3D printing technology, and does not make too many changes to the preparation and pyrolysis process of the existing glassy carbon bracket, nor does it require the assistance of special processes. It only uses a unique three-periodic minimal surface lattice design. Therefore, the production process of this superstructure glassy carbon material is simple and easy to achieve mass production.
[0044] (3) The superstructured glassy carbon prepared by the present invention can be further prepared into large-sized products (from millimeter level to decimeter level) or complex microscopic products (from nanometer level to micrometer level). It also has excellent mechanical properties and low density, low resistance, high temperature resistance, corrosion resistance and other characteristics, and can be well applied in the fields of energy, aerospace, biomedicine and even art decoration.
[0045] (4) The superstructure glassy carbon prepared by the present invention can be modularly divided to achieve an assembled design, and can be modularly assembled with other materials such as metals and polymers to form a composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.
[0047] Figure 1 A model diagram of a three-periodic minimal surface lattice structure (support structure) provided for one of the embodiments of the present invention; Figure 2 A schematic diagram of the structure of a three-periodic minimal surface lattice structure in three directions of XYZ provided by one of the embodiments of the present invention; Figure 3 This is a physical picture of centimeter-scale superstructure glassy carbon prepared in one of the embodiments of the present invention; Figure 4 This is a verification diagram of the thermal shrinkage performance of common structural glassy carbon prepared in one of the comparative examples of the present invention; Figure 5 A verification diagram showing that the superstructured carbons of different sizes prepared by the method of the present invention all have the ability to shrink in equal proportions (A is the shrinkage of glassy carbons of different sizes in equal proportions after high-temperature pyrolysis under the same conditions, and B is the shrinkage rate of glassy carbons of different sizes in different directions); Figure 6 Schematic diagram of large defects and deformation of glassy carbon scaffolds prepared by ordinary methods and ordinary structures (A is ordinary scaffolding structure glassy carbon, B is ordinary regular octahedral structure glassy carbon, C is the SEM image of ordinary scaffolding structure glassy carbon defects, and D is the SEM image of ordinary regular octahedral structure glassy carbon defects); Figure 7Scanning electron microscope images of microscopic defects of different glassy carbon materials (A is the superstructure glassy carbon of the present invention, B is the common structure glassy carbon, and the scale bars are both 200 μm); Figure 8 The microstructure and defect analysis of large-scale superstructure carbon (A is a high-resolution TEM image of superstructure glassy carbon, with scale bars of 5nm and 2nm, B is a cross-sectional SEM image and cross-sectional TEM image of superstructure glassy carbon, with scale bars of 50μm and 100nm); Fig. 9 This is the maximum compressive strength result diagram of different glassy carbon materials; Fig.10 To verify that the superstructure glassy carbon of the present invention has excellent mechanical properties; Fig.11 The stress distribution diagram of the finite element analysis of the three-periodic minimal surface lattice structure proposed by the present invention; Fig.12 Finite element analysis of other structures (A is the finite element analysis of ordinary scaffolding structure, B is the finite element analysis of ordinary regular octahedron structure); Fig.13 A schematic diagram of the complex shape of the microscopic superstructure glassy carbon prepared by the present invention (the scale bars are 2 μm and 5 μm); Fig.14 The maximum compressive strength and maximum strain results of the microscopic glassy carbon prepared in the present invention (the scale bar is 1 μm); Fig.15 The elastic test results of the microscopic glassy carbon prepared by the present invention (the scale bar is 1 μm); Fig.16 TEM image of superstructured carbon at microscopic size (scale bar is 5 nm); Fig.17 A schematic diagram of the complex shape of the large-scale superstructure glassy carbon prepared by the present invention (the scale bar is 1 cm); Fig.18 This is a rendering of the modular segmentation design of the superstructure glassy carbon prepared by the present invention; Fig.19 Schematic diagram of coating the PEEK coating on the surface of superstructure glassy carbon; Fig. 20 Schematic diagram of the composite of superstructured glassy carbon surface and hydroxyapatite. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0049] Herein "and / or" includes any and all combinations of one or more of the associated listed items.
[0050] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.
[0051] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.
[0052] In this specification, some embodiments may be disclosed in a format of being in a range. It should be understood that this description of "being in a range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values within this range. For example, the description of the range 1-6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as individual numbers within this range, such as 1, 2, 3, 4, 5 and 6. Regardless of the breadth of the range, the above rules apply.
[0053] Definition of noun: The “uniform distribution of stress in all directions” mentioned in the present invention means that the static stress analysis results in the X, Y and Z directions of the three-periodic minimal surface lattice structure of the present invention all show uniform static stress distribution.
[0054] The "superstructure" mentioned in the present invention refers to a structure that simultaneously satisfies the three-periodic minimal surface mentioned in the present invention and the stable structure with uniform stress of diamond or diamond-like carbon.
[0055] The "diamond-like structure" described in the present invention refers to a modification of a regular tetrahedral structure similar to diamond, wherein the modification includes a slight change in bond angle or edge length.
[0056] The “proportional reduction” mentioned in the present invention means that during the pyrolysis change of the three-periodic minimal surface structure described in the present invention, the shrinkage rate in each direction is the same or close.
[0057] Embodiment 1: This embodiment provides a method for preparing a superstructure glassy carbon material, the process of which is: firstly designing a three-periodic minimal surface lattice superstructure, and then preparing it using 3D printing technology.
[0058] The three-periodic minimal surface (TPMS) described in the present invention is a minimal surface with a crystal structure, which periodically (periodic changes along the X, Y, and Z axes) constructs a smooth, fully connected porous structure in three-dimensional space, with an average curvature range of -0.135 to 0.137, and an optimal average curvature of 0.
[0059] This embodiment provides four three-dimensional digital models of three-periodic minimal surface lattice structures, namely D type, G type, CY type and IWP type.
[0060] The specific preparation process includes the following steps.
[0061] Step 1: Use 3D modeling software to design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure. The three-dimensional digital model equations involved (hereinafter referred to as "equations") are as follows.
[0062] (1) Type D: Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z)=0 (2) Type G: cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0 (3) CY type: sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 (4) IWP type: 2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x))–(cos(2x) + cos(2y)+cos(2z))=0.3 The D type is preferred in this embodiment. The three-periodic minimal surface lattice model (bracket structure model) designed according to the D type equation is as follows: Figure 1 Further, the schematic diagram of the structure of the three-periodic minimal surface lattice model in the X, Y, and Z directions is shown in Figure 2 .
[0063] Step 2: Using a carbon-rich polymer as a printing material, specifically epoxy resin is used as the material in this embodiment, and a polymer bracket, also called a superstructure bracket, is obtained by printing using digital light processing printing technology (photocuring printing).
[0064] Step three: Use a muffle furnace, a tubular furnace, a hot isostatic pressing sintering furnace and other equipment to heat the superstructure bracket prepared in step two at normal pressure under the protection of an inert gas, argon. Specifically, first heat from room temperature to 250°C for 60 minutes, then heat to 350°C for 100 minutes, keep warm for 120 minutes, then heat by 1 degree every 2 minutes to 700-3000°C, then cool naturally, and the superstructure bracket is proportionally reduced to obtain a superstructure glassy carbon material. The superstructure glassy carbon prepared in this embodiment has a porous structure with a specification size exceeding 5cm, a pore wall thickness of the porous structure less than 3mm, and a porosity greater than 50%. The centimeter-level superstructure glassy carbon prepared in this embodiment can be seen Figure 3 .
[0065] It is to be understood that the present invention can also use furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin, polylactic acid, polycaprolactone, polyethylene, polyetheretherketone, nylon, polycarbonate, polymethyl methacrylate, polyvinyl butyral, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene chloride, polystyrene, polybutadiene, polyphenylene oxide, polyphenylene sulfide, polybutene-1, polybenzimidazole, polyaryletherketone, polyarylsulfone, polyethylene naphthalate, polyaniline, polyethylene glycol, polyethylene terephthalate ... One or more materials selected from the group consisting of poly(p-phenylene), polyphthalimide, poly(phenylene vinylene), polylactide, polychloroprene, cyanoacrylate, poly(naphthylene vinylene), poly(p-xylene), poly(methylphenylsiloxane), liquid crystal polymer, polythiophene, polyvinyl acetylene, polyoxadiazole, polybisphenol A, polyacrylonitrile-butadiene-styrene copolymer, polychlorotrifluoroethylene, polyepoxy-acrylate copolymer, polybenzoquinone, poly(p-phenylene sulfone), polyphenylene, polybenzoxazole, polypiperidine, polyvinyl acetal, polybenzothiazole or polyvinyl pyrrolidone are used as 3D printing materials.
[0066] It is understandable that the present invention may also adopt 3D printing technologies such as liquid crystal display printing technology, two-photon printing technology, extrusion printing technology, and powder laser sintering printing.
[0067] It is understandable that the present invention may also use inert gases such as nitrogen, helium or neon or a combination thereof as the protective gas.
[0068] Example 2 The performance verification of the superstructure glassy carbon material prepared in Example 1 is provided.
[0069] 2.1 Shrinkage determination The shrinkage rate of the superstructure glassy carbon prepared in Example 1 was measured, and the results showed that the superstructure glassy carbon prepared in Example 1 did not show the phenomenon of uneven shrinkage and stress concentration.
[0070] Control experiment: The ordinary structural glassy carbon precursor was first heated from room temperature to 250°C for 60 minutes, then heated to 350°C for 100 minutes, kept warm for 120 minutes, then heated to 700-3000°C for 2 minutes per degree, and then cooled naturally. The shrinkage rate was then measured, and the results showed obvious shrinkage unevenness and stress concentration, such as Figure 4 shown.
[0071] 2.2 Proportional shrinkage verification Superstructure glassy carbon of different sizes was prepared by the method of Example 1, and then the uniform shrinkage test of the glassy carbon bracket was carried out. The results are as follows: Figure 5 shown. Figure 5 As can be seen in A, after high-temperature pyrolysis under the same conditions, glassy carbons of different sizes shrink in equal proportions and their shapes do not change. Figure 5 B shows the shrinkage of glassy carbon with different sizes in different directions.
[0072] The appearance and microscopic morphology of the ordinary glassy carbon prepared in the control experiment of 2.1 were observed. The results are as follows Figure 6 shown. Figure 6 It can be seen that the ordinary glassy carbon stent prepared by a method other than the method of the present invention exhibits obvious deformation and large defects after shrinkage.
[0073] 2.3 Microstructure observation The ultrastructured glassy carbon prepared in Example 1 and the common structured glassy carbon prepared in the control experiment 2.1 were analyzed by scanning electron microscopy for apparent microscopic defects, such as Figure 7 Obvious surface cracks were observed on the ordinary structural glassy carbon, but no similar defects were found on the super-structured glassy carbon prepared in Example 1. Figure 8 , the figure shows that the superstructure glassy carbon prepared by the present invention has no defects larger than micrometer level.
[0074] 2.4 Mechanical properties verification The superstructure glassy carbon prepared in Example 1 and the common structure glassy carbon prepared in the control experiment 2.1 were subjected to compression test, and the specific steps are as follows.
[0075] 1cm × 1cm × 1cm glassy carbon material samples were prepared and the maximum compressive strength of the samples was tested using a universal mechanical compressor. The displacement rate of the compressor beam was set to 1mm / min until the sample was broken and the maximum load was recorded. The ratio of the maximum load to the force-bearing area was the maximum compressive strength.
[0076] The experimental results are as follows Fig. 9 The maximum compressive strength of the superstructure glassy carbon material sample prepared in Example 1 is 186 MPa, while the maximum compressive strength of the common structure glassy carbon material sample is only 17.59 MPa.
[0077] It is further verified that the superstructure glassy carbon material prepared in Example 1 has excellent mechanical properties, and only 0.1g can withstand a weight of 100kg. Fig.10 .
[0078] Example 3 This embodiment provides several other examples of preparation methods of superstructure glassy carbon materials, which are as follows.
[0079] Example 1 Step 1: Use 3D modeling software to design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure. The three-dimensional digital model equations involved (hereinafter referred to as "equations") are as follows.
[0080] (1) Type D: Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z)=0 (2) Type G: cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0 (3) CY type: sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 (4) IWP type: 2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x))–(cos(2x)+cos(2y)+cos(2z))=0.3 In this example, type D is preferred.
[0081] Step 2: Use a carbon-rich polymer as the printing material. In this example, furfuryl alcohol resin is used as the material. The polymer scaffold, also known as the superstructure scaffold, is printed using two-photon printing technology.
[0082] Step 3: Use a muffle furnace, a tubular furnace, a hot isostatic pressing sintering furnace and other equipment to heat the superstructure bracket prepared in step 2 at normal pressure under the protection of inert gas argon. Specifically, first heat from room temperature to 250°C for 70 minutes, then heat to 350°C for 80 minutes, keep warm for 100 minutes, then heat by 1 degree every 3 minutes to 700-3000°C, and then cool naturally to prepare a superstructure glassy carbon material.
[0083] Example 2 Step 1: Use 3D modeling software to design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure. In this example, type D is preferred.
[0084] Step 2: Use a carbon-rich polymer as the printing material. In this example, acrylic resin is used as the material. The polymer bracket, also known as the superstructure bracket, is printed through extrusion printing technology.
[0085] Step 3: Use a muffle furnace, a tubular furnace, a hot isostatic pressing sintering furnace and other equipment to heat the superstructure bracket prepared in step 2 at normal pressure under the protection of inert gas argon. Specifically, first heat from room temperature to 255°C for 100 minutes, then heat to 360°C for 100 minutes, keep warm for 80 minutes, then heat by 1 degree every 5 minutes to 700-3000°C, and then cool naturally to prepare a superstructure glassy carbon material.
[0086] Example 3 Step 1: Use 3D modeling software to design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure. In this example, type D is preferred.
[0087] Step 2: Use a carbon-rich polymer as the printing material. This example uses polyurethane as the material and prints a polymer scaffold, also known as a superstructure scaffold, through powder laser sintering printing technology.
[0088] Step 3: Use a muffle furnace, a tubular furnace, a hot isostatic pressing sintering furnace and other equipment to heat the superstructure bracket prepared in step 2 at normal pressure under the protection of inert gas argon. Specifically, first heat from room temperature to 260°C for 90 minutes, then heat to 360°C for 90 minutes, keep warm for 120 minutes, then heat by 1 degree every minute to 700-3000°C, and then cool naturally to prepare a superstructure glassy carbon material.
[0089] It should be noted that the above embodiments are merely examples, and are based on the final sintered superstructure glassy carbon material, rather than limitations.
[0090] Example 4 Further description of the four three-periodic minimal surface models involved in Example 1 is provided.
[0091] The four three-periodic minimal surface models are all based on the definition of three-periodic minimal surfaces. Their common point is that they all have periodic structural repetition in three dimensions, and the average curvature ranges from -0.135 to 0.137.
[0092] More intuitively, the average curvature of each point on the surface is 0.
[0093] Furthermore, this structure with zero curvature has isotropic and uniform stress distribution.
[0094] Therefore, the glassy carbon prepared based on the three-dimensional digital models of the four three-periodic minimal surface equations provided in Example 1 all have the characteristics of large size and super structure.
[0095] Finite element simulation of the three-periodic minimal surface structure of the D-type equation was performed using ABAQUS software. Fig.11 . During the simulation, HyperMesh was used for pre-processing and ABAQUS was used for solving. Pre-processing includes geometric processing and removal of some very small features that do not affect the calculation results. Then a mesh size of 0.4mm was used to generate the mesh, using second-order tetrahedral elements. The total number of elements is 400,814 and the number of nodes is 617,725. The material is set as an elastic-plastic material with a density of 1.1g / cm³, a Young's modulus of 11GPa, and a Poisson's ratio of 0.4. One end of the structure is completely fixed, and a 5% compressive strain is applied in three different lattice directions (X, Y, and Z). The stress distribution under compressive strain in different directions was calculated. The results show that when strain is applied in each direction, the model has a uniform stress distribution as a whole, and there is no stress concentration phenomenon. In addition, Fig.11 The lower right picture shows that this three-period minimal surface lattice structure shrinks proportionally after pyrolysis to form superstructure glassy carbon.
[0096] Compared with the finite element analysis of other structures, it can be seen that other structures may have stress concentration phenomenon, see Fig.12 .
[0097] Example 5 The superstructure glassy carbon proposed in the present invention can also be prepared into other materials, and this embodiment only shows some examples.
[0098] In some embodiments, the superstructure glassy carbon provided by the present invention can be prepared as a microscopically complex structure (microscopic size) material, wherein the specifications of the microscopically complex structure material include nanoscale or microscale.
[0099] Specifically: S01: Design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure, the three-dimensional digital model includes (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3; S02: using the three-dimensional digital model designed and constructed in S01 as a template to perform two-photon printing, using materials including polymers to obtain a polymer scaffold; S03: The polymer support obtained in S02 is sintered in vacuum or inert gas at normal pressure. The sintering temperature conditions are similar to those in Example 1 to obtain microscopic superstructure glassy carbon, which is further prepared into a specific shape. For example, see Fig.13 .
[0100] The mechanical properties and elasticity of the micro-sized superstructure glassy carbon were further tested, and the results are shown in Fig.14 and Fig.15 The results show that the maximum compressive strength of microscopic glassy carbon is 7.23 GPa, and the maximum strain is 66%; it also has ultra-high elastic deformation recovery ability, with a maximum elastic recovery strain of 25%.
[0101] Further characterization of the microscopic superstructure glassy carbon material is shown in Fig.16 A large number of curled graphene sheet structures can be seen in its TEM image, indicating enhanced mechanical properties.
[0102] In some embodiments, the superstructure glassy carbon proposed in the present invention can also be prepared into large-scale complex structure materials by photocuring printing. Fig.17 .
[0103] In some embodiments, the superstructure glassy carbon proposed in the present invention can also be modularly divided into designs, see Fig.18 . In some embodiments, the superstructure glassy carbon of the present invention can also be compounded with a polymer material. For example, a PEEK coating is applied to the surface of the superstructure glassy carbon. Fig.19 The figure shows a coating prepared by a 1% PEEK dispersion and a coating prepared by a 2% PEEK dispersion. For another example, the superstructure glassy carbon proposed in the present invention can also be compounded with hydroxyapatite (ceramic material), see Fig. 20 , composite materials can be further used in energy, aerospace, biomedicine and other fields It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0104] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A porous support structure, characterized in that: The porous support structure has a stable structure with uniform stress distribution in all directions; the porous support structure uses a unit cell of a three-periodic minimal surface as a minimum repeating unit; the unit cell of the three-periodic minimal surface includes a diamond or diamond-like structure; and the material constituting the porous support structure is a high molecular polymer.
2. The porous scaffold structure according to claim 1, characterized in that: The three-periodic minimal surface includes a digital model that satisfies the following characteristics: (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.
3.
3. The porous scaffold structure according to claim 1, characterized in that: The high molecular polymer includes a high molecular polymer with a high carbon content.
4. The porous scaffold structure according to claim 3, characterized in that: The high molecular polymer with high carbon content comprises furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin, polylactic acid, polycaprolactone, polyethylene, polyetheretherketone, nylon, polycarbonate, polymethyl methacrylate, polyvinyl butyral, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene chloride, polystyrene, polybutadiene, polyphenylene ether, polyphenylene sulfide, polybutene-1, polybenzimidazole, polyaryletherketone, polyarylsulfone, polyethylene naphthalate, polyaniline, poly One or more materials selected from the group consisting of acetylene, polyparaphenylene, polyphthalimide, polyphenylene vinylene, polylactide, polychloroprene, cyanoacrylate, polynaphthylene vinylene, polyparaxylene, polymethylphenylsiloxane, liquid crystal polymer, polythiophene, polyvinyl acetylene, polyoxadiazole, polybisphenol A, polyacrylonitrile-butadiene-styrene copolymer, polychlorotrifluoroethylene, polyepoxy resin-acrylate copolymer, polybenzoquinone, polyparaphenylene sulfone, polyphenylene, polybenzoxazole, polypiperidine, polyvinyl acetal, polybenzothiazole and polyvinyl pyrrolidone.
5. A superstructure glassy carbon, characterized in that: The superstructure glassy carbon is obtained by pyrolyzing the porous support structure described in any one of claims 1 to 4 and then carbonizing it in proportion; the pyrolysis conditions include vacuum high-temperature pyrolysis or high-temperature and normal-pressure pyrolysis under an inert atmosphere.
6. A superstructure glassy carbon, characterized in that: The superstructure glassy carbon has a stable structure with uniformly distributed stress in all directions; the superstructure glassy carbon uses a unit cell of a three-period minimal surface as a minimum repeating unit; the unit cell of the three-period minimal surface includes a diamond or diamond-like structure; preferably, the surface average curvature of the three-period minimal surface structure ranges from -0.135 to 0.
137.
7. The superstructure glassy carbon according to claim 6, characterized in that: The three-periodic minimal surface includes a digital model that satisfies the following characteristics: (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.
3.
8. The superstructure glassy carbon according to claim 7, characterized in that: The superstructure glassy carbon is obtained by pyrolyzing a high molecular polymer scaffold having the same structural unit and then carbonizing it in equal proportion; the pyrolysis conditions include vacuum high-temperature pyrolysis or high-temperature and normal-pressure pyrolysis in an inert atmosphere.
9. Use of the superstructure glassy carbon according to claim 5 or any one of claims 6 to 8 in preparing large-size materials, characterized in that: The specifications of the large-size material are from millimeter level to decimeter level; or, the use of the superstructure glassy carbon described in claim 5 or any one of claims 6-8 in the preparation of microscopic complex structure materials is characterized in that the specifications of the microscopic complex structure materials are from nanometer level to millimeter level.
10. The use according to claim 9, characterized in that The large-size materials include large-size glassy carbon materials and composite materials of large-size glassy carbon and other materials; the other materials include metal materials, polymer materials, ceramic materials, glass materials or semiconductor materials.
11. Use of the superstructure glassy carbon according to claim 5 or any one of claims 6 to 8 in the preparation of energy materials.
Citation Information
Patent Citations
Preparation method of large-size medical glass carbon block material
CN116143519A
Mesh glassy carbon and preparation method thereof
CN116495720A
3D printed controllable porous hydroxyapatite bioceramic stent and preparation method thereof
CN110272273A
Foam-filled three-period minimum-curved-surface porous structure sandwich panel and preparation method thereof
CN110641083A
Preparation method of elastomeric polymer with three-period extremely-small curved surface structure
CN116238149A
Cited By
Superstructural glassy carbon, preparation method therefor and use thereof
WO2026026814A1